Global Networks and Religious Dynamics: Reading the Hikayat Raja Pasai of Pre-Colonial Malay-Archipelago - Burhanuddin, Jajat (Studia Islamika, 2025)
This article examines Hikayat Raja Pasai, a fourteenth century Malay text, to understand the emergence of a global network that played a crucial role in the Islamization of Malay-Archipelago. This text provides us with a historical narrative on the engagement of northern Sumatra, the site of Samudra Pasai kingdom, with Islamic global networks, particularly international Muslim merchants. This network became the primary influence in the thought of both ruling elites and people of the kingdom. This article emphasizes that this global network provided momentum for the Malay people to embrace a new religious faith, Islam, amidst an emerging cosmopolitan lifestyle and to obtain economic advantage out of their involvement in the burgeoning maritime commerce. The Hikayat Raja Pasai, therefore, helps explain the continued growth of Islam over the course of northern Sumatra’s history. Keywords: Hikayat Raja Pasai, Islam, Global Network, Trade, Politics, Samudra Pasai.